1980-ЖЫЛЛАРДАҒЫ ҚАРАҚАЛПАҚ ПРОЗАСЫНДА ЎAҚЫT ҲӘМ КЕҢИСЛИК ОБРАЗЛАРЫ (К.Алламбергенов ҳәм О.Әбдирахманов шығармалары мысалында) - Сагидуллаева, Ж.Н. (FAN va JAMIYAT, 2020)
Тhis article is devoted to one of the most important and insufficienty explored problems in Karakalpak literature. The article examines the role of the chronotope (time and space) in the Karakalpak prose of the 80s of the last century. This problem is investigated using the example of prose works of talented writers like K.Allambergenov and U.Abdirakhmanov. The article reveals the role of the chronotope of the road and the chronotope of the threshold in the poetic work of art in relation to the realities of writer’s period and style. The types of chronotope (closed and open space, implicit form) and their function in the structure of the work of art are also analyzed.